1986
DOI: 10.1007/bf00199366
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin-induced augmentation of lymphoproliferative responses in patients with head and neck cancer

Abstract: Augmentation of the phytohemagglutinin (PHA)-induced lymphoproliferation of peripheral blood mononuclear cells by indomethacin, a drug which blocks prostaglandin (PG) synthesis, was assessed in 37 patients with squamous cell carcinoma of the head and neck. Indomethacin enhanced the uptake of 3H-thymidine in stimulated cultures both from patients and normal individuals. However, because lymphoid cells from cancer patients were less reactive than those from normal controls, the proportionate increase in PHA-stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 32 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…In this study, we report on sila-substituted derivatives of indomethacin (Figure 1), an NSAID indicated for use in rheumatoid arthritis, ankylosing spondylitis, and osteoarthritis. Indomethacin has demonstrated activity in the treatment and prevention of human cancer [16][17][18][19] however, side effects have limited the use of indomethacin in cancer patients. In an effort to improve the safety and biological activity of indomethacin, an organosilicon fragment was introduced in indomethacin by converting the carboxylic acid group into a sila-amide ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we report on sila-substituted derivatives of indomethacin (Figure 1), an NSAID indicated for use in rheumatoid arthritis, ankylosing spondylitis, and osteoarthritis. Indomethacin has demonstrated activity in the treatment and prevention of human cancer [16][17][18][19] however, side effects have limited the use of indomethacin in cancer patients. In an effort to improve the safety and biological activity of indomethacin, an organosilicon fragment was introduced in indomethacin by converting the carboxylic acid group into a sila-amide ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Studies with animal tumor models have dem onstrated promising results of immunothera py with IL-2 and LAK cells [7][8][9], However, clinical trials have shown that the use of IL-2 and LAK cells is only effective in the treat ment of some patients with metastatic renal cell carcinoma or with malignant melanoma [10][11][12], Therefore, one of our research goals is to search for the agents which modify IL-2-induced LAK cell activity in order to in crease the effectiveness of adoptive immuno therapy for cancer [13][14][15], Indomethacin, a cyclooxygenase inhibitor, is a documented immune modulator that upregulates immune function by suppressing the biosynthesis of the immunosuppressive agent, prostaglandin E2 (PGE2) [16][17][18][19], In combination with IL-2, indomethacin has been used in vitro to augment LAK cell activi ty generated from lymphoid cells [20][21][22][23][24] and in vivo in advanced melanoma patients [25], although it is more commonly used for the purpose of preventing a side effect of IL-2 administration, e.g. fever and chills [10][11][12],…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently reported immunologic abnormality in tumor-bearing patients is the decreased lymphocyte blastogenic response to mitogen stimulation. This impairment in blastogenesis has been reported in patients with head and neck, lung, and colon carcinomas and in patients with melanomas [3][4][5][6][7]14,15]. These studies also demonstrated that either addition of indomethacin to the lymphocyte cultures or removal of the monocyteimacrophage cells corrected the impairment in lymphocyte blastogenesis.…”
Section: Discussionmentioning
confidence: 87%